Mucosal Immunity: Lessons from the Lower Respiratory and Small Intestinal Epithelia - Kayle B. Dickson; Andrew W. Stadnyk; Juan Zhou; Christian Lehmann (Biomedicines)
Mucosal epithelia represent a diverse group of tissues that function as a barrier against the external environment and exert a wide variety of tissue-specific secondary functions. This review focuses on the lower respiratory tract and small intestinal epithelia, which serve as two distinct sites within the body with respect to their physiological functions. This review provides an overview of their physiology, including both physiological and mechanical defense systems, and their immune responses, which allow both tissues to tolerate commensal organisms while mounting a response against potential pathogens. By highlighting the commonalities and differences across the two tissue types, opportunities to learn from these tissues emerge, which can inform the development of novel therapeutic strategies that harness the unique properties of mucosal epithelia.